Ddb1 Is Essential for the Expansion of CD4+ Helper T Cells by Regulating Cell Cycle Progression and Cell Death - Yang, Lingtao; Chen, Wei; Li, Li; Xiao, Yueyue; Fan, Shilin; Zhang, Quan; Xia, Tian; Li, Mengjie; Hong, Yazhen; Zhao, Tongjin; Li, Qiyuan; Liu, Wen-Hsien; et al. (Frontiers in Immunology, 2021)
Follicular Helper T (TFH) cells are specialized CD4+ helper T cells that provide help to B cells in humoral immunity. However, the molecular mechanism underlying generation of TFH cells is incompletely understood. Here we reported that Damage-specific DNA binding protein 1 (Ddb1) was required for expansion of CD4+ helper T cells including TFH and Th1 cells, germinal center response and antibody response to acute viral infection. Ddb1 deficiency in activated CD4+ T cells resulted in cell cycle arrest at G2-M phase and increased cell death, due to accumulation of DNA damage and hyperactivation of ATM/ATR-Chk1 signaling. Moreover, mice with deletion of both Cul4a and Cul4b in activated CD4+ T cells phenocopied Ddb1-deficient mice, suggesting that E3 ligase-dependent function of Ddb1 was crucial for genome maintenance and helper T cell generation. Therefore, our results indicate that Ddb1 is an essential positive regulator in the expansion of CD4+ helper T cells.